Induction and restriction as adjoint functors on representations of locally compact groups - Robert A. Bekes; Peter J. Hilton (International Journal of Mathematics and Mathematical Sciences)
In this paper the Frobenius Reciprocity Theorem for locally compact groups is looked at from a category theoretic point of view.